KAJIAN TEO-SEKSUAL LONTAR RAHASYA SANGGAMA - Wardana, Kadek Agus; Donder, I Ketut; Suwantana, I Gede (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Sex is an inseparable part of human life. Even so, sex has not been fully understood because more people view sex as something sacred and secret so that sex is only interpreted as a taboo or prohibition to be taught. That is the way of the past view of sex, but lately many parties view sex education is important. Because it is very warmly discussed later. During this time sexuality is often understood as something taboo to talk about especially if it is associated with religion. Of course there are many who refuse to discuss porn in a religious context. Hinduism provides a different view of sexuality. In Hinduism sexuality is seen as a sacred thing in human life because it is implicitly contained in the purusÄrtha chess teachings, namely dharma, artha, kama, and moksa. One of the goals of human life is the fulfillment of lust or desire (kama) which encourages people to do something that makes people excited in this life. Sex which is equated with kama in Sanskrit and Old Javanese has a place in human life. It cannot be eliminated just behind the current time, because it continues to flow as an instrument of strength to obtain the highest virtue.